أثر التغيير التنظيمي على عملية اتخاذ القرارات الإدارية دراسة ميدانية على المستشفيات العامة الليبية العاملة بمدينة بنغازي - بشير محمد العبار , (Scientific Journal of University of Benghazi, 2020)
This study aimed to identify the effect of organizational changing its dimensios (structural change, behavioral change, technical change) on the process of making administrative decisions in Libyan public hospitals operating in the city of Benghazi. To achieve the objectives of the study, the researchers followed the descriptive analytical method, and used the questionnaire form as the main tool in data collection. The study population consisted of all the senior and middle managers of the number (95) . The researchers studied it completely using the comprehensive inventory method, and also used the Statistical Package Program (spps) in data analysis. The study reached many results, the most important of which are :The level of organizational change was high and the degree of making administrative decisions has been mediummm and there is a strong correlation between organizational changing and its dimensions taken together and the process of making administrative decisions, There is also a statistically significant strong influence between organizational changing and its dimensions taken together on the process of making administrative decision , and a strong statistically significant impact between dimensions (structural change, behavioral change) on the process of the making administrative decisions,The study made Some recommendations that will contribute to enhance the effect of s organizational changing on the process of making administrative decisions in the in Libyan public hospitals.